Implementasi Smart Brankas Berbasis Internet Of Things Pada PT. Umbi Teknologi Indonesia - Farrois Qithfirul Aziz; Afu Ichsan Pradana; Dwi Hartanti (Fakultas Teknik Universitas Hamzanwadi, 2024)
The IoT-based smart safe represents a cutting-edge innovation in secure valuables storage. The aim of this research is to develop, implement and evaluate an intelligent and secure system connected to the Internet of Things (IoT). The development method involves the integration of hardware and software design with sensor technology and network connectivity. Implementation is achieved by deploying the smart safe within home or office environments connected to the internet. System evaluation is conducted through a series of tests focusing on security, functionality, and reliability. The research findings demonstrate that IoT-based smart safes offer enhanced security access, real-time monitoring, and user convenience through mobile applications. These findings have significant implications for improving secure storage across various contexts, from households to businesses